Effect of restricted feeding on compensatory growth responses in Clarias gariepinus (Burchell, 1822) - Ali, M Z; Jauncey, K (Indian Journal of Fisheries, 2011)
A four week feeding trial was carried out in a recycling water sytem to investigatethe effect of restricted feeding regimes on compensatory growth and bodycomposition in African catfish, Clarias gariepinus . A fishmeal-based diet containing35% protein and 18 kJ g-1 gross energy (GE) was fed to triplicate groupsof 30 fish. Fish were fed in five feeding schedules of 28 days : restricted 14 days+ appetite 14 days; restricted 7 days + appetite 7 days; restricted 3 days + appetite4 days; restricted 2 days + appetite 2 days. The restricted regime was achievedby feeding at the rate of 1% (maintenance ration) of their body weight per day,adjuted after weekly weighing. African catfish did not exhibit compansatorygrowth response under alternating periods of a feed restriction and appetitefeeding. However, not sifnificant (P>0.05) values of feed and protein utilizationwere found under alternating periods of feed restriction and appetite feeding.Significantly higher (P0.05) on body composition, organ indices, evisceratedcarcass composition, viscera lipid and liver lipid. This study reveals thatC. gariepinus failed to display compensatory growth response by alternatingperiods of restricted and appetite feeding.